Optimization of the Four Wheel Patrol of Sabhara Unit to Prevent The Crime of Vehicle Theft Actions to Realizing a Conductive Kamtibmas Under The Law of Medan Polrestabes - Gery Barloy Pangestu (Advances in Police Science Research Journal, 2021)
This research is based on high number of cases of motor vehicle theft compared to other crimes in Medan resort police. Police need to carry out patrols to prevent the meeting of intentions and opportunities for criminals, especially in motor vehicle theft. Therefore, the purpose of this study is to describe the efforts of the sabhara unit and the factors that influence the implementation of patrols and harkamtibmas efforts in optimizing the four wheel patrol. This type of research uses field research and a qualitative approach. Sources of data include primary data and secondary data with data collection techniques used are interviews, observations, document studies and Focus Group Discussions. Data analysis techniques used include data reduction, data presentation and drawing conclusions. The analytical knife in conducting the discussion includes management theory and crime prevention theory. The results of the study found that the crime of theft until now is the highest crime in Medan resort police. Patrol activities carried out by the Medan resort police Sabhara Unit are carried out according to the SOP, divided into 3 stages, namely preparation, implementation and termination. Judging from several aspects, the implementation of patrols in the Sabhara is considered less than optimal, influenced by several factors. The most influential internal factor is the problem of the limited number of communication tools such as Handy Talk (HT) and the external is the lack of community participation. Harkamtibmas efforts in optimizing the R4 patrol carried out a strong point, but the strong implementation did not meet the principle of crime prevention, namely the patrol did not interact with the community and did not give advice to the community. Based on the results of the study, the authors suggest that in making patrol routes always pay attention to the development of the latest Kamtibmas situation in Medan City. In order to apply for additional HT, often establish collaborations with the community, such as the Hansip post, Kamra post, Security guard post, and Kamling post selectively to facilitate monitoring of locations prone to motor vehicle theft and patrolling through residential areas